The war on sex - Halperin, David M.; Hoppe, Trevor (Duke University Press, 2017)
The new pariahs : sex, crime, and punishment in America / Roger N. Lancaster -- Sympathy for the devil : why progressives haven't helped the sex offender, why they should, and how they can / Judith Levine -- Queer disavowal : controversial crimes and building abolition / Owen Daniel McCarter, Erica R. Meiners, and R Noll -- A new iron closet : failing to extend the spirit of Lawrence v. Texas to prisons and prisoners / J. Wallace Borchert -- Seeing the sex and Justice landscape through the Vatican's eyes : the war on gender and the seamless garment of sexual rights / Mary Anne Case -- Sex panic, psychiatry, and the expansion of the carceral state / Regina Kunzel -- The creation of the modern sex offender / Scott De Orio -- For what they might do : a sex offender exception to the Constitution / Laura Mansnerus -- The "hooker teacher" tells all / Melissa Petro -- Carceral politics as gender justice? The "traffic in women" and neoliberal circuits of crime, sex, and rights / Elizabeth Bernstein -- California's Proposition 35 and the trouble with trafficking / Carol Queen and Penelope Saunders -- HIV : prosecution or prevention? HIV is not a crime / Sean Strub -- HIV monsters : gay men, intentional HIV infection, and the new political economy of HIV / Gregory Tomso -- HIV care as social rehabilitation : medical governance, the AIDS surveillance industry, and therapeutic citizenship in neoliberal Taiwan / Hans Tao-Ming Huang -- The new war on sex : a report from the global front lines / Maurice Tomlinson -- Building a movement for justice : Doe v. Jindal and the campaign against Louisiana's crime Against nature statute / Alexis Agathocleous -- Bringing sex to the table of justice / Amber Hollibaugh